Role of Technology in Activity Based Learning (Trinity Journal of Management, IT & Media (TJMITM), 2011)
In the nntton whose Ed11cnlion Systom Is suffonng from  two ma1or problems of mutigmdo r!Rs.c;room tonching &  lns11fhcicnt stRffmg. Acttv,f} Btiscd LcRmmg(ABL) Is one  of the now rovo/ut,on m th dm. t,on. II off, rs solutions  to both th s major problem.,;. Hero the system is  student ntn , i t oft mphRsts is lmd on the ubiquitous  I 9ming I nm the /:lsr n of R teacher. Here a lot also  d p nd. l n th t hnology as well The basic aim of this  paper ,s h ht1Qht the various ways in which the  t :hn I g) cRn be helpful ,n implementation of actiVity  oo~ f m,ng in the held of Professional Education
Keywords: Activity Based Learning ABL; multtgrade classrooms; faculty develooment; technology in ABL